2013
DOI: 10.1093/plankt/fbt023
|View full text |Cite
|
Sign up to set email alerts
|

Microzooplankton grazing in the oceans: impacts, data variability, knowledge gaps and future directions

Abstract: Here we review all published data on phytoplankton growth and microzooplankton grazing using the dilution technique to better understand the role of this group of grazers in different regions of the oceans, and to identify the knowledge gaps that require future efforts. A total of 1525 data points assimilated from 110 studies were included and grouped using the biogeographic subsets defined by Longhurst et al. [(1995) An estimate of global primary production in the ocean from satellite radiometer data. J. Plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
189
6
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(218 citation statements)
references
References 100 publications
19
189
6
4
Order By: Relevance
“…All the µ (except those obtained at KJ53 during the winter cruise) and m were within the reviewed ranges based on global data collection Schmoker et al, 2013). Substantive m but negative µ were observed at KJ53 (Fig.…”
Section: Comparisons With Other Studiessupporting
confidence: 64%
See 2 more Smart Citations
“…All the µ (except those obtained at KJ53 during the winter cruise) and m were within the reviewed ranges based on global data collection Schmoker et al, 2013). Substantive m but negative µ were observed at KJ53 (Fig.…”
Section: Comparisons With Other Studiessupporting
confidence: 64%
“…Phytoplankton provides almost all of the primary production in the upper ocean. Microzooplankton (< 200 µm) consumes most of the daily primary production in the sea, and regulates phytoplankton community composition, and affects the ultimate fate of the phytoplankton-derived primary production (Banse, 2007(Banse, , 2013Landry and Calbet, 2004;Schmoker et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a cross-compilation of 66 studies, Calbet and Landry (2004) revealed that grazing loss accounts for 60 -75% of daily phytoplankton production, and is higher in estuarine and coastal waters than in oceanic waters. Although it is generally accepted that grazing loss is higher in productive waters (Schmoker et al 2013), the impact of grazing loss is still not clear as grazing loss rates are extremely variable, are sitespecific and can be affected by multiple environmental drivers e.g. temperature (Irwin andOliver 2009, Boyce et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Other than filling an obvious data gap (Schmoker et al 2013), it is vital to investigate the phytoplankton production and grazing loss in tropical waters in view of the current global climate change (IPCC 2007). Ocean warming is expected to have the strongest 10 effect in tropical waters where most organisms are already functioning at or near optimum temperatures (Pomeroy and Wiebe 2001).…”
mentioning
confidence: 99%